Evelyn Blackwood & Saskia E. Wieringa (eds.): Female Desires. Samesex Relations and Transgender Practices Across Cultures: Anmeldes af Yvonne Mørck - Mørck, Yvonne (Tidsskriftet Antropologi, 1999)
Samesex Relations and Transgender Practices Across Cultures. Anmeldes af Yvonne Mørck